Análise de filtros planares sobre substratos têxteis - Oliveira, Wisla Milena Morais de (Universidade Federal Rural do Semi-Árido, 2018)
The development of planar circuits in flexible materials has been a field of research of great interest for telecommunications researchers. Therefore, this article presents an analysis on the applicability of textile materials as substrate of microstrip planar circuits. Thus, a band pass filter and a band reject were designed and made. These, were developed for applications in wireless systems in the Industrial Scientific and Medical band (ISM) and WiMax band. The whole analysis was carried out by means of a bibliographical survey on the behavior of these structures, as well as through simulations carried out in Ansoft HFSS software of Ansys Company. The filters were constructed on a textile substrate made of acrylic fibers, to later carry out the experiments through the vector network analyzer (VNA). The theoretical results and tested were satisfactory, being possible to reach a expected frequency response, even the high tangent of losses and low dielectric permissiveness that the tissue used has.
Monografia
Keywords: Filtros planares; Materiais flexíveis; Substrato têxtil; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA